Abortspørsmålets politiske historie 1900-2020 - Elvbakken, Kari Tove (Scandinavian University Press (Universitetsforlaget), 2021)
This book explores the political history of abortion in Norway from the beginning of the 1900s up to the present day. Applying a historically oriented political science perspective, it offers an analysis of recurring mobilization efforts to obtain legal abortion, and the many political processes that followed in their wake. Empirical sources such as documents from the political processes, various archival material, as well as publications from conferences, women organizations, newspapers and journals are analysed. The book shows that the labour women's movement contributed decisively to the legalization of abortion before the new women's movement emerged in the early 1970s. Abortion has been characterized by sharp conflicts throughout the 1900s, and remains so to this day.